APPLICATIONS OF ACTIVE METHODOLOGIES IN SPECIAL EDUCATION FOR THE PROMOTION OF AUTONOMY AND SCHOOL INCLUSION - Pimentel, Adele Emília Schlukat; Marques, Fabiane Regina Geraldes Moreira; Mariano, Hosana de Queiroz; Bastos, Iraneide Targino; Ribeiro, Líbia Raquel Gomes Vicente; Moreira, Lucilda Alves Moraes; Almeida, Rita de Cássia da Costa Sousa; de Ataides, Wedna Lima (Seven Editora, 2025)
This article aims to analyze the contributions of active methodologies to the teaching and learning process of students with disabilities, focusing on the promotion of school inclusion and student protagonism in basic education. The research is characterized as qualitative, theoretical, and bibliographic, based on the analysis of contemporary publications that address the practical application of these methodologies in the context of special education. The study seeks to avoid approaches centered on the philosophical foundations of active pedagogies, such as Dewey’s classical formulations, and instead focuses on concrete pedagogical practices and strategies, such as flipped classroom, gamification, and project-based learning. The results indicate that the adoption of active methodologies fosters the development of autonomy among students with disabilities, expands opportunities for participation in school activities, and contributes to the construction of inclusive environments. It is concluded that, although structural and training challenges persist, the implementation of active methodologies offers promising paths toward a more equitable education that is responsive to diversity.DOI: https://doi.org/10.56238/sevened2025.038-046